Strategi Coffee Shop di Palangka Raya dalam Meningkatkan Penjualan di Era Digital - Luluk Tri Harinie; Aprilita A; Atry Tresya Widastuti; Elisabet Maria Rensiana Anggaed Anggae; Imron Rosyadi; Ivana Angelita; Lala L; Muhammad Ilham Rizky Saputra; Nursyifa Tiara Ameilia; Oscario O; Owen Juniarko; Putri Dahlia (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to analyze the strategies used by Kongkow By Lau Sabaru Coffee Shop in Palangka Raya in increasing their sales in the digital era. The research method used was purposive sampling, where data was collected through interviews with coffee shop owners, as well as direct observation of the strategies implemented. This research provides an overview of the challenges faced by coffee shops in facing increasingly fierce competition in the food and beverage industry. The results of the study show that Kongkow By Lau Sabaru has adopted several effective strategies to increase their sales in the digital era. These strategies include using social media, content marketing, and working with digital partners. In this case, the coffee shop has used social media such as Instagram to broaden the reach of potential customers and build a strong brand image. Apart from that, creative and engaging content marketing is also an important part of their strategy, which helps to attract customers. The results of this study can provide valuable insights for other coffee shop owners and management in developing effective marketing strategies in the digital era.Â